OPERATIONAL WORK OF A SQUID TRANSPORTING SHIP CASE STUDY ON KM PERINIS JAYA 89 - Ikhsan, Suci Asrina; Sari, Iya Purnama; Widagdo, Aris; Djunaidi, Djunaidi; Sumitro, Martinus Robinson; Aidil, Fikri (Politeknik Kelautan dan Perikanan Dumai, 2025)
Carrier vessels play a crucial role in the capture fisheries industry, particularly as transportation modes responsible for delivering harvested products from fishing grounds to the shore or port. This strategic function requires the implementation of clear Standard Operating Procedures (SOPs) to ensure that handling practices comply with regulations and meet quality standards. Therefore, assessing the application of SOPs on squid carrier vessels is essential to determine the extent to which existing procedures align with proper handling standards and regulatory requirements. The objective of this study is to evaluate the conformity of SOP implementation on squid carrier vessels with applicable regulations, identify weaknesses or inconsistencies in operational practices, and provide recommendations for improvements that may enhance product quality, operational efficiency, and the sustainability of fisheries enterprises. This research was conducted from March to May 2025, using KM Perintis Jaya 89 as the research object, a squid carrier vessel owned by Perintis Jaya International operating in Benoa, Bali. Data collection was carried out through direct observation during the vessel’s operational trips, including documentation of the number of trips, travel duration, cargo volume, and fuel consumption. The main focus of the assessment was the handling of squid, encompassing loading, storage, and unloading activities carried out by the carrier vessel. The findings indicate that KM Perintis Jaya 89 has implemented SOPs in accordance with policy directives. Proper and consistent SOP implementation supports effective and efficient vessel operations, thereby ensuring the maintained quality of squid products destined for market distribution.